COCONUT SHELL BIOBRIQUETTES TRAINING TO THE COMMUNITY OF KARANG KEMIRI, BELITANG, OGAN KOMERING ULU TIMUR REGENCY, SOUTH SUMATERA - Alieftiyani Paramita Gobel; Yandriani Yandriani; Hairunnisa Van Gobel (Universitas Ahmad Dahlan, 2021)
The utilization of technology becomes an indicator of the growth of a society that solves problems, needs, benefits in an effective, efficient and sustainable ways. One of the technologies utilized by the community to reduce the massive exploitation of non-renewable fossil energy is to reuse alternative energy. Biobriquette becomes alternative energy from biomass waste that is possibly used in daily activities. In response to this, the purposes of performing the Community Service Program (PPM) in Karang Kemiri Village, Belitang District are; to 1) provide counseling and assistance to the community in creating biobriquette from coconut shells, 2) apply biobriquette in the cooking process. The PPM implementation method includes 3 (three) stages, that is socialization, biobriquette production, and biobriquette application. Based on the results achieved as a whole, the local Community welcomed the Community Service Program as it provides them new knowledge and skills regarding biobriquette creation. The other result of this community service program is to apply biobriquette instead of firewood to cook for their daily cooking needs